Effectiveness and Safety of Iguratimod Monotherapy or Combined With Methotrexate in Treating Rheumatoid Arthritis: A Systematic Review and Meta-Analysis - Ouyang, Dan; Ma, Yuan Zhi; Zou, Jie; Wang, Yong Long; Chen, Zheng; Yang, Yu Ying; Zou, Bin; Li, Xin; Cao, Jian Zhong (Frontiers in Pharmacology, 2022)
Objectives: We aimed to estimate the effectiveness and safety of iguratimod monotherapy or combined with methotrexate in treating rheumatoid arthritis to provide an evidence-primarily based foundation for clinical application. Methods: We used eight databases and two clinical trial websites to search for randomized controlled trials from conception to March 15, 2022, based on outcomes of patients with RA treated with IGU. The evidence quality assessment of primary outcomes was evaluated by GRADE tool, RevMan 5.3, and StataMP 14.0 was used to perform this research. Results: A total of 4261 patients with RA from 39 RCTs was included in this research. Pooled results demonstrated as follows: 1) Compared with Methotrexate (MTX) alone, the ACR20 of IGU alone was higher, while the ACR50 and ACR70 have no significant difference, furthermore, the DAS28 was lower. 2) Compared with MTX alone, the ACR20, ACR50, and ACR70 of IGU + MTX was higher, while the DAS28 was lower. 3) Compared with MTX + leflunomide, the ACR20, ACR50, ACR70 and DAS28 of IGU + MTX have no significant difference. 4) Compared with MTX + hydroxychloroquine, the DAS28 of IGU + MTX was lower. 5) Compared with MTX + tripterygium glycosides, the DAS28 of IGU + MTX was lower. 6) The results of safety analysis showed no significant differences in adverse events among groups. However, the incidence of AEs in the IGU + MTX group was lower than MTX + LEF. Conclusion: Compared with original therapy, IGU alone or in combination with MTX may have superior efficacy with acceptable safety. Even if the intervention lasts for 52 weeks, the curative effect can still be achieved without obvious adverse events (AEs). Notably, it outperformed the control group within 12 weeks, even if it took at least 12 weeks to improve the DAS28 (Mu et al., 2021; Zeng et al., 2021). Furthermore, it displayed preferable efficacy and safety in refractory and first-visit RA, as well as elderly and young and middle-aged RA, indicating that IGU alone or in combination with MTX was a comparable strategy to the original treatment, regardless of the age, course, or stage of the RA.